MAPEAMENTO DE PERCEPÇÕES SOBRE A IMPLANTAÇÃO E EXECUÇÃO DO BALANCED SCORECARD EM PEQUENAS EMPRESAS DA CIDADE DE JUIZ DE FORA MG - Croce Filho, Jair (2009)
In the review of the literature found some texts that describe thoughts about the impact of the implementation of Balanced Scorecard (BSC) in large companies. But these texts do not present a description of a systematic method for mapping the positive effects and difficulties of implementing the BSC. This paper aims to present a systematic survey of the perceptions of managers of small companies on the deployment and execution of the BSC in its business. The reason for the removal of this information is to increase the chances of success and survival of small businesses in a highly competitive environment, as this methodology has been widely used by large corporations as a tool for improvement of organizational performance with great success. To achieve the goal was made a field research, supported by a collection built specifically for this purpose. Data were collected from twelve to small businesses located in the city of Juiz de Fora, southeastern Brazil, from February to August 2008. The data obtained allowed to identify the main positive effects and the main difficulties associated with the implementation of BSC and contribute to the construction of knowledge in an area not explored and may help with this category of company managers in increasing the competitiveness.